PENGARUH PENYULUHAN MENGGUNAKAN MEDIA RODA PUTAR TERHADAP PENGETAHUAN KARIES GIGI PADA MURID KELAS III DAN IV SDN GAMBUT II - Nur’aien Istiqayani Salsabila; Ida Rahmawati; Isnawati Isnawati (Poltekkes Kemenkes Banjarmasin, 2020)
A children group with 8 to 10 years of aged (3 to 4 elementary school grades) is a naive and a real thinking period of time, it’s also a periode of time to gather knowledge, and a games is chosen as a tool that is in accordance with the target, so that dental and oral health education can produce behavioral changes for them as a target. The results from an observation of a preliminary study that had been done on 10 students in SDN Gambut 11, consist of 6 students from the third grade and the rest 4 students from the fourth, resulted an average def-t was 3.8 and 6.2 an average DMF-T rate. This study aims to determine whether there is an influence of counseling using a rotary wheel media on dental caries knowledge for the third and fourth grade students of SDN Gambut 11. The research design using